At what price? Labour politics and calculative power struggles in on-demand food delivery. (1st January 2020) - Doorn, Niels van
Abstract : This article asks what can be gained by making calculability a pivotal demand for wage politics in gig economies characterised by dynamic fee structures. It examines how a small group of Berlin-based food delivery workers attempted to challenge Deliveroo's market power by building their own makeshift calculative equipment to help them 'reverse engineer' the company's fee pricing algorithm. It then documents the difficulties these 'riders' experienced when attempting to translate their fight for calculable earnings into a more comprehensive labour politics. Finally, the article addresses the limits of market-based struggles over calculative power, against the background of a still pervasive 'platform exceptionalism': a socio-legal imaginary that treats platform companies as unique business entities, enabling them to engage in regulatory arbitrage while contractually enforcing the subordination and rightlessness of gig workers.